2019 11th International Conference on Virtual Worlds and Games for Serious Applications (VS-Games) 2019
DOI: 10.1109/vs-games.2019.8864576
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serious Gaming using Virtual Reality Applications for 3D Architectural Visualization

Abstract: This paper investigates the advantage of VR technology in architectural education. Different studies showed that VR increases the engagement and motivation of students by creating an interactive environment and provides deeper learning. On the other hand, Precedents in architecture are the first and the most important step toward architectural education. One needs to study these precedents and store them in the experiential/episodic memory. Visiting precedents is more beneficial than conventional ways of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…However, more appealing gameplay experiences were reported by IVR game users compared to tablet computer users. Kharvari and Hohl (2019) tested a prototype IVR game, Therme Vals, for architectural education and found that students were able to recall spatial configuration of the simulated building without physically visiting the site. They claimed that VR could be a simpler, cheaper, safe and effective way of accumulating 'highly specific architectural knowledge' compared to site visits.…”
Section: Immersive Virtual Reality Games (Ivr Games)mentioning
confidence: 99%
“…However, more appealing gameplay experiences were reported by IVR game users compared to tablet computer users. Kharvari and Hohl (2019) tested a prototype IVR game, Therme Vals, for architectural education and found that students were able to recall spatial configuration of the simulated building without physically visiting the site. They claimed that VR could be a simpler, cheaper, safe and effective way of accumulating 'highly specific architectural knowledge' compared to site visits.…”
Section: Immersive Virtual Reality Games (Ivr Games)mentioning
confidence: 99%
“…Virtual environment makes the students more attentive by establishing the interactive environment that helps to reveal the results of interaction immediately which accomplish the goal of learning by doing [14]. A collector game for architectural education to learn the precedents of architecture was introduced in [15] where the students were trained to use episodic memory appropriately to remember spatial configurations and doing the proper use of episodic memory to store the cubes for later use.…”
Section: Vr In Educationmentioning
confidence: 99%
“…By doing so students would be able to explore and apply what they have built up in civil Engineering situations. Likewise, Kharvari and Hohl [65] used virtual reality methods for reproducing the virtual form of a building for architecture students to study the precedents of a particular structure without the need for a field visit. The fact that virtual reality is capable of replicating how lightning behaves in a room also favours lightning education as proposed by Boyles et al [66].…”
Section: Virtual Reality In Educationmentioning
confidence: 99%